Beyond survival: unraveling the dynamics of Ebola virus resurgence in Sub-Saharan Africa and the remarkable journey of survivors - Asare Fenteng, Eric; Ossei, Paul Poku Sampene; Ayibor, William Gilbert; Narh-Bedu, Tracy (Frontiers in Virology, 2023)
Ebola virus disease (EVD) remains a significant public health threat, with sporadic outbreaks occurring in Sub-Saharan Africa. Survivors of EVD may experience various post-infection symptoms, collectively known as post-Ebola virus syndrome (PES), which include chronic arthralgia, uveitis, headache, and psychosocial stressors. In this review, we discuss the persistence of Ebola virus in survivors and its possible role in the reemergence of current outbreaks. We highlight that waning immunity of survivors enhances viral persistence and may lead to viral reactivation and recurrence of disease in previously affected tissues. The delicate equilibrium between diminished immune cell surveillance and limited viral replication may lead to enduring chronic inflammation.Our systematic review, based on an extensive survivor cohort, underscores the importance of continued research and preparedness efforts to combat future outbreaks through adequate surveillance and timely public health interventions. This review serves as a comprehensive guide to understanding the complexities of EVD survivorship, the challenges of PES, and the strategies to mitigate its impact.